G143(P) Ethnic inequalities in paediatric burns: Findings from a systematic review and analyses of hospital episodes statistics data from 2009 to 2015. (24th May 2017) - Ikpeme, MJ; Emond, AM; Mytton, JA; Hollen, L
Abstract : Aim: To outline observable inequalities in paediatric burn injuries across different ethnicities in some high income countries Methods: A systematic review was done to reveal current knowledge and gaps in available and published research on burn epidemiology in the UK and some high income countries within North America, Australasia and Europe. The PECO framework includes children aged 0–16 years old, with accidental burn injuries and outcomes reported as quantitative data using terms like epidemiology, prevalence and incidence etc. Hospital Episodes Statistics (HES) analyses identified 40 172 burn cases of which 36 080 were primary burn admissions. A comparator group of 'other conditions' was developed for inferential analyses comprising a random mixture of 1% of other primary admissions in HES from 2009–2015 (1 24 841 controls). Descriptive analyses were via STATA14 and Microsoft Office tools. Inferential analyses employed multivariate logistic regression via STATA V14. Variables of interest were 82% to 100% complete. Results: 6638 papers were retrieved from 7 databases. 110 studies were eligible for narrative synthesis. Strength of evidence describing the association between ethnicity and burns in children was moderate. 26 of 110 studies (24%) reported this relationship. Using the Critical Appraisal Skills Programme (CASP) tool; 1 systematic review, 4 cohort, 1 case control, 2 prospective cross sectional and 44% of the 18 retrospective cross sectional studies used had low risk of bias. Of the 26 studies, 53.8% used hospital data alone while 57.7% claimed their samples were representative of their population. 19.2% of studies mention confounding of low socio-economic status on those from an indigenous/minority ethnicity. No study reported health seeking behaviour by ethnicity. 11.7% of studies reported first aid use but this was unclassified by ethnic or racial categories. Children from minority/indigenous backgrounds often had larger, deeper burns, more severe burns or longer length of stay (LOS). From the HES data analyses, Black/Black British children had the highest OR for burn admissions, AOR=1.50 (95% CI: 1.42–1.59). Conclusions: These findings provide brief insights of the contribution of one's ethnicity on burn admissions risk in children aged 0–15 years in England. These will assist in identifying groups more at risk for suitable interventions and aid preventive measures overtime.